How much can reticulate evolution entangle plant systematics? Revisiting subfamilial classification of the Malvatheca clade (Malvaceae) on the basis of phylogenomics - Luna, Gustavo; Costa, Lucas; Pezzini, Flávia Fonseca; Karimi, Nisa; Strijk, Joeri Sergej; Carvalho-Sobrinho, Jefferson; Colli-Silva, Matheus; Marques, André; Souza, Gustavo (Frontiers in Plant Science, 2026)
Reticulate evolution (RE), involving hybridization and related processes, generates network-like rather than strictly bifurcating relationships among lineages and can obscure phylogenetic relationships. Detecting ancient hybridization is particularly challenging, as genomic signals may erode over time. The Malvatheca clade (Malvaceae), marked by multiple paleopolyploidy events since it’s estimated origin 66 my, offers a useful model for examining RE. Its three subfamilies—Bombacoideae (with high chromosome numbers, mostly trees), Malvoideae (lower chromosome numbers, mostly herbs), and the recently described Matisioideae—show unresolved relationships, with several taxa of uncertain placement. We conducted a phylogenomic analysis of 69 Malvatheca species via complete plastomes, 35S rDNA cistrons, nuclear low copy genes and comparative repeatome data. Most of the datasets consistently resolved four clades: (I) Bombacoideae, (II) Malvoideae, (III) Matisioideae, and (IV) a heterogeneous assemblage including representatives of Malvoideae, Matisioideae and several incertae sedis taxa. Chromosome numbers were negatively correlated with repeatome diversity: Bombacoideae presented higher counts but lower repeat diversity, possibly reflecting slower repeat evolution associated with woody growth forms. In contrast, clades III and IV showed marked heterogeneity in both chromosome number and repeat composition, which is consistent with a reticulate origin. Overall, our results show evidence of ancient hybridization and polyploidy in shaping Malvatheca evolution. These results highlight that reticulation and genome dynamics, rather than taxonomic boundaries alone, are central to understanding the diversification of Malvatheca.